Obstructive Biliary Cirrhosis in a Cat Due to Platynosomum Fastosum Infection - Soto, Jorge A.; Villalobos, Amri; Arraga de Alvarado, Cruz M.; Chirinos, Angel R. (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Biliary cirrhosis is rare in domestic animals and has scarcely been reported in cats. Most cases of biliary cirrhosis in cats are related to parasitic infections by Amphimerus pseudofelineus, Metorchis complexus, and Opistorchis pseudofelineus. A case of obstructive biliary cirrhosis caused by a severe infection by the liver fluke Platynosomum fastosum and its gross and microscopic lesions are describe in a ca't.